From a hefty greenery to a parched paradise: assessing the impacts of climate change on water security and biodiversity decline in the Western Cape Province of South Africa - Mbana, Zenande; Simatele, Mulala Danny (Frontiers in Environmental Science, 2026)
BackgroundThis systematic review integrates existing evidence within a multi-scale analytical framework to understand how climate-induced water stress affects biodiversity in Mediterranean-climate regions, using Erica species in the Cape Floristic Region (CFR) as a model system.MethodsFollowing PRISMA guidelines, we systematically reviewed 57 peer-reviewed articles from Scopus and Google Scholar, organizing findings using the DPSIR (Drivers-Pressures-State-Impacts-Responses) framework across three spatial scales: global Mediterranean, regional Sub-Saharan Africa, and local Cape Floristic Region.Results and DiscussionSystematic synthesis reveals water availability as the primary mechanism mediating climate impacts on Erica biodiversity across all examined contexts. Integration of quantitative evidence from multiple independent studies identifies threshold patterns where water deficits of 20%–30% relative to historical conditions distinguish resilient from vulnerable populations in European systems, though documented thresholds vary among populations (20%–40% range) and require validation for CFR endemic species. Cascading impacts progress from physiological stress (40% flowering reduction under experimental drought) through demographic bottlenecks (50%–70% germination decline under moisture limitation) to ecosystem functional changes. While physiological response mechanisms operate consistently across Mediterranean regions, vulnerability magnitude is context-dependent: synthesis suggests CFR’s approximately 700 endemic species exhibit narrower tolerances than European congeners, reflecting evolution under stable climatic conditions versus historical variability. This multi-scale framework distinguishes generalizable physiological principles from context-specific vulnerabilities, providing operational guidance for conservation priority-setting. The DPSIR structure explicitly traces causal pathways from global drivers to local responses, enabling identification of intervention leverage points across organizational levels from regional water policy through landscape connectivity to site-scale microhabitat management. Findings indicate that conservation strategies developed for European Erica populations may underestimate CFR vulnerabilities without accounting for narrower endemic tolerances and limited adaptive capacity arising from rapid recent diversification.